The Use of Innovative Technologies in the Process of Teaching the Russian Language - Chulyukina, Elena Evgenievna (International Journal on Orange Technologies, 2023)
The Russian language is an educational subject, the cognitive value of which is extremely high: thinking is formed at such lessons, a sense of love for the native language is instilled, universal values are comprehended through language, personality is brought up, the intellectual development of the child takes place with the help of language, the assimilation of all other academic disciplines. The humanity of society, expressed through language teaching, consists in the desire to expand the scope of knowledge, raise the bar for the intellectual development of the student.